Padding performance according to impact conditions and cycle of use in ski areas - Marine Dorsemaine; Catherine Masson; Serge Riveill; Pierre-Jean Arnoux (JSAMS Plus, 2023)
Objective: Collisions with obstacles are among the most severe accidents recorded in ski areas. In France, the padding placed on these obstacles conforms to a design standard to assess its ability to dissipate energy when impacted by a skier/snowboarder. Padding performance, i.e. its ability to prevent or mitigate injuries and the changes in performance over time remain poorly understood. Considering the global objective to explore the padding's ability to protect from injuries during its cycle of use, a large experimental campaign was designed to investigate various padding performance. Design: Experimental drop tests were performed on padding in ski areas using instrumented head and trunk impactors. Method: The influences of the padding's properties (thickness, age, impact location, cover), environment (temperature, position on the obstacle) and impact conditions (speed, impactor) on head and chest accelerations were investigated. 180 drop tests were performed on 40 padding samples (with thicknesses ranging from 10 ​cm to 30 ​cm) with ages varying from 0 to 17 years old. Results: This study showed a significant influence of speed, impactor and the padding's thickness (P ​< ​0.001) and also position. However, temperature, aging, impact location and cover type did not have a clear influence on impact accelerations for these impact conditions. Conclusions: This study is an innovative step towards a better understanding of ski padding performance and behavior. These results provide quantitative information for the development of best practices aiming at ski areas increasing safety on their slopes. They also highlight challenges and perspectives for the design of future padding.